2015
DOI: 10.1007/s00432-015-2021-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and number of circulating tumour cells and microemboli at diagnosis of advanced NSCLC

Abstract: CTC can be detected in two-thirds and CTM in more than half of patients with advanced NSCLC at diagnosis. Reasons underlying lack of CTC and CTM in some advanced lung cancers deserve further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 20 publications
5
37
1
Order By: Relevance
“…This could partly be explained by the subjective nature of the method of identification, particularly in the absence of any special or specific antibody stains. However, our detection rates were similar in comparison to studies looking at patients with more advanced NSCLC with 60% for both Pathologists, although it must be noted the advanced cancer sample numbers comprised a very small proportion of the cohort, Mascalchi et al (2015) reported detection rates of CTCs using ScreenCell of 65% in a cohort of 26 patients with stage III and IV NSCLC. The authors found no correlation between tumour stage and the number of CTCs detected (27).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This could partly be explained by the subjective nature of the method of identification, particularly in the absence of any special or specific antibody stains. However, our detection rates were similar in comparison to studies looking at patients with more advanced NSCLC with 60% for both Pathologists, although it must be noted the advanced cancer sample numbers comprised a very small proportion of the cohort, Mascalchi et al (2015) reported detection rates of CTCs using ScreenCell of 65% in a cohort of 26 patients with stage III and IV NSCLC. The authors found no correlation between tumour stage and the number of CTCs detected (27).…”
Section: Discussionsupporting
confidence: 78%
“…However, our detection rates were similar in comparison to studies looking at patients with more advanced NSCLC with 60% for both Pathologists, although it must be noted the advanced cancer sample numbers comprised a very small proportion of the cohort, Mascalchi et al (2015) reported detection rates of CTCs using ScreenCell of 65% in a cohort of 26 patients with stage III and IV NSCLC. The authors found no correlation between tumour stage and the number of CTCs detected (27). Our detection rates, in comparison to other studies, support the idea that the release of CTCs is not related to tumour stage.…”
Section: Discussionsupporting
confidence: 78%
“…We did not find any correlation or association of CTCs/CTM with white blood cells (leukocyte, neutrophil, or lymphocyte). Additionally, there was no significant correlation between CTC number and CTM number in our study as in a previous study of non-small cell lung cancer (23 ). The disparity in the range of CTC numbers of PDAC and other cancers might have originated from tumor characteristics and the platforms used.…”
Section: Discussioncontrasting
confidence: 59%
“…ScreenCell Âź technology is a range of specific devices and has been validated for the detection and molecular analysis of CTCs in several other solid tumors including prostate, pancreatic cancer, renal, colon, and lung [16,17,18,19,20,21]. Without surface-marker selection, size-execution method allows the capture of all types of circulating tumor associated cells in one blood draw and exploring the phenotypic and genetic heterogeneity of these cells.…”
Section: Introductionmentioning
confidence: 99%